Study of association of urine albumin to creatinine ratio with endothelial dysfunction in HIV patients on HAART - Sharana Basava Hoskera; Avinash Hanbe Rajanna; Nitish Ashok Gurav; Ashok ML (Asian Journal of Medical Sciences, 2021)
Background: In HIV (Human immunodeficiency virus) positive patients several factors have been proposed to explain the cardiovascular (CV) risk, which include pro-athero-thrombotic viral effect, infection-mediated immune dysfunction and possible effects of HAART(Highly active antiretroviral therapy). Presence of endothelial dysfunction, an early CV risk marker, in HIV-infected patients on long-term HAART. Endothelial dysfunction can be measured by bFMD (Brachial artery flow mediated vasodilatation). Urine albumin to creatinine ratio (UACR) is frequent in HIV patients and is predictor of cardiovascular risk. UACR and endothelial dysfunction are positively associated in HIV affected patients thereby increased UACR might help to identify endothelial dysfunction in HIV patients on HAART.